GATA2 rs2335052 Polymorphism Predicts the Survival of Patients with Colorectal Cancer - Liu, Xijuan (PLoS One, 2015)
BACKGROUND: GATA binding protein 2 (GATA2) is a transcription factor that has essential roles in hematologic malignancies and progression of various solid tumors. Our previous studies suggested that high GATA2 expression is associated with recurrence of colorectal cancer (CRC). However, the influence of GATA2 single nucleotide polymorphisms (SNPs) on the survival of CRC remains unknown. METHODS: We genotyped GATA2 SNP rs2335052 using Sanger sequencing after PCR amplification, and determined GATA2 expression by immunohistochemistry in a cohort of 180 CRC patients. Kaplan-Meier survival analysis and Cox proportional hazard regression were used to analyze the association between the GATA2 rs2335052 genotypes and the clinical outcome of CRC. RESULTS: We found that there was no significant correlation between the rs2335052 genotypes and the expression of GATA2. However, the Kaplan-Meier survival analysis suggested that the carriers of the A-allele of SNP rs2335052 were significantly associated with increased risk of recurrence and reduced disease-free survival (DFS), compared with those carrying the variant genotype of GG in rs2335052 (P = 0.021). Moreover, univariate and multivariate Cox regression analyses revealed that GATA2 SNP rs2335052 was an independent risk factor for the DFS of CRC patients. CONCLUSION: Our results demonstrated that GATA2 SNP rs2335052 is an independent predictor for prognosis of CRC patients. This raised the possibility that SNP rs2335052 may serve as a potential indicator for predicting recurrence of CRC after curative colectomy.